Effect Of Cooling Rate On Microstructures And Mechanical Properties Of C102 Copper Alloy - Ridhwan, J.; Hafidzal, M.H.M; Zakaria, Mohamad Shukri; Muhammad, Syafiq (Fakulti Kejuruteraan Mekanikal (FKM), Universiti Teknikal Malaysia Melaka (UTeM), 2014)
The objective of this study is to illustrate the effect of two types of heat treatment on microstructure and mechanical properties of C102 copper alloy. Annealing and quenching were conducted to study the effect of cooling rate on material. Specimens were heated at 350, 400 and 500oC and were cooled by using two types of cooling medium; furnace cooling and water quench. Tensile strength of 254.6 MPa was obtained for the asreceived specimen. It was shown that an increase in cooling rate contributed to a higher strength due to local strain effect. Rapid cooling in quenched specimen had successfully increase the hardness by 41% and recorded the highest tensile strength of 359 MPa while slow cooling rate which experienced by an annealed specimen resulted in the lowest tensile strength of 136 MPa. Microstructure investigation shows annealed specimen produced coarse austenitic structure with larger grain size. Meanwhile, quenched specimen produced finer austenitic structure with smaller grain size. It was observed that the grain size of annealed specimen was increased with soaking temperature, however, quenched specimen shows the other way around.